Culturally Relevant Dialogic Reading Curriculum for Counselors: Supporting Literacy and Social-Emotional Development. Issue 1 (2nd January 2018) - Cook, Amy L.; Fettig, Angel; Morizio, Laura J.; Brodsky, Lauren M.; Gould, Kaitlin M.
Abstract : Social-emotional learning (SEL) and literacy skills are key components of child development. School counselors are charged with supporting children's holistic development to prepare them for adulthood by implementing counseling curricula that focus on both academic and social-emotional growth. School counselors can promote academic and literacy learning by engaging children in counseling techniques that employ shared reading. Through reading and discussing socially and culturally meaningful texts, children make personal connections with characters in stories, thereby strengthening a love for reading. Creating personal connections to stories also helps develop children's SEL. This article describes using dialogic reading as a culturally relevant counseling practice to promote SEL and support literacy development for kindergarten through third grade children. Dialogic reading is a shared reading strategy that positions children as active participants in adult-guided book reading and builds literacy and social-emotional skills. The dialogic reading curriculum described in this article is designed for school counselors given their unique skill set in promoting children's SEL and academic development. There are limited interventions available for school counselors that combine SEL and literacy skill development through culturally responsive practices. Implications of infusing culturally relevant dialogic reading in counseling to promote SEL and literacy learning are described.